"A GROUP OF LIKE‐MINDED LADS IN HEAVEN": EVERYDAYNESS AND THE PRODUCTION OF DUBAI SPACE. Issue 2 (15th December 2013) - KANNA, AHMED; Hourani, Najib B.; Kanna, Ahmed
ABSTRACT While the Arab Gulf's imperial geography has been recognized at the level of geopolitics, little if any work has connected empire to the daily, human geographies of the region. Scholarship on the intersection between urbanism and empire has tended to emphasize issues of surveillance and governance, assuming, whether intentionally or not, an imperial, "birds‐eye" point of view. Such an approach both leaves much interesting material out of the analytical frame and privileges so‐called central or major imperial cities. This essay proposes another frame for imperial urbanism, based upon Lefebvre's related notions the "production of space" and "everyday space." The author takes as a case study the city of Dubai, and specifically its spaces of "bourgeois gratification"—"British pubs, " gated communities, shopping malls, and resorts. He argues that these demonstrate how the city has been as profoundly shaped by its imperial legacy as have more recognizable imperial cities. Dubai today, and for a long time, has been a place where British and other Western expatriates feel that they can "escape" the stresses and constraints of life in the West. He shows that this is as much a product of the imperial encounter as are more recognizable products of empire, for example monumental architecture.